Identification of failure root causes using condition based monitoring data on a 33 kV switchgear - Bakar, Ab Halim Abu; Illias, Hazlee Azil; Othman, M.K.; Mokhlis, Hazlie (International Journal of Electrical Power & Energy Systems, 2013)
The implementation of condition based monitoring (CBM) involves variety of disciplines, such as failure analysis, on-line diagnostics, diagnostic data interpretation, management and communication, corrective actions and program maintenance. However, the most important tasks for a comprehensive CBM analysis are to identify the actual root cause that contributes to equipment failure and the selection of appropriate mitigation techniques to address the root cause of the failure. In this paper, CBM actual site data of a 33 kV switchgear from an electrical utility company in Malaysia (from 2007 to 2010) were used to develop failure root causes database. The database was used to identify the possible root cause of a failure and to propose a failure mitigation plan for any CBM activity. The CBM data were obtained using ultrasound, thermoscanning and transient earth voltage (TEV) methods at different compartments of the switchgear, which yielded specific root causes of failure. In order to verify the effectiveness of the proposed method, the method was tested using actual site data obtained in 2011. Using the proposed method, the actual root cause of a failure can be identified quickly; hence the time and cost of repairs can be reduced.